Finding the "local green voice"? - Turan, Zeynep (Urbani izziv, 2018)
The Gowanus neighbourhood, like many other New York City waterfronts, is facing a crossroads: how to promote development in a polluted landscape vulnerable to climate-induced sea-level rise that is inhabited by low-income populations and coveted by wealthy new arrivals for its waterfront property? For many years, toxic contamination and a combined sewer overflow problem inhibited new development in the neighbourhood. But in recent years, particularly beginning in 2010, after the Environmental Protection Agency designated the Canal and surrounding areas a Superfund site targeted for clean-up, developers have sought to shed Gowanu's industrial identity and recast it as a prime up-and-coming residential locale. Although the community celebrates environmental restoration and protection, there is also a sense of foreboding that clean-up is paving the way for high-end development projects. This article charts the progress of neoliberal urban development in Gowanus through the lens of critical urban theory, identifying stakeholders and power dynamics. It looks at rezoning/revitalization as a tool of the municipality to transform an industrial business zone and low-income neighbourhood, ostensibly to foster development and cope with climate change and sea-level rise, but, in fact, cultivates socio-political exclusion and gentrification while ignoring concerns over the long-term environmental viability of new development.
Keywords: critical urban theory; gentrification; javni prostori; participacija; participatory planning; rezoning; waterfronts